Using Public-Private Partnership for Stimulating Innovational Developments in the Infrastructural Sphere - MOROZOVA, Irina; LITVINOVA, Tatiana; MORDVINTSEV, Ivan A.; KONINA, Olga V. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The purpose of the article is to study the perspectives of using public-private partnership for stimulating innovational developments in the infrastructural sphere of modern Russia. The method of factor analysis is used for determining the influence of such factors as infrastructure, institutes, and innovations on the value of the global competitiveness index of Russia in 2016, as compared to 2012. The information and analytical basis includes materials of the Global competitiveness report for 2012 and 2016. The results of analysis showed importance of development of infrastructural sphere in modern Russia, as it is one of the key factors of the national economy’s competitiveness. That’s why its development is very important for strengthening of national competitive advantages of Russia. The authors offer a perspective scheme of using public-private partnership for stimulating innovational developments in the modern Russia’s infrastructural sphere.